Application of phosphorous fertilizer to increase the production of several parijoto (Medinilla speciosa Blume) accessions - Indah Fatika Sari; Muhammad Ahmad Chozin; Dwi Guntoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Parijoto fruit (Medinilla speciosa Blume) is a plant known as a medicinal plant in Indonesia. Parijoto fruit production is still low. Phosphorous (P) fertilization can enhance fruit production, but the optimal dosage for parijoto has yet to be determined. The research objective was to obtain the P fertilizer dosage to improve the production of several parijoto accessions. The research was conducted from January to June 2023 at Agribusiness and Technology Park IPB. The study used a split-plot randomized complete block design with four replications. The main plot's accession factor consisted of Bogor, Kudus, and Nganjuk. The fertilizer dosage per polybag, as the subplot, consisted of without P2O5 (P0), 1.8 g P2O5 (P1), 3.6 g P2O5 (P2), 5.4 g P2O5 (P3), 7.2 g P2O5 (P4), 9.0 g P2O5 (P5). The results showed that applying P fertilizer at 7.2 g P2O5 produced the highest fruit weight per plant for the Bogor and Nganjuk accessions. For the Kudus accession, it was at a fertilization dosage of 5.4 grams of P2O5. There was an interaction between accession and P dosage on fruit weight per plant. Keywords: dosage; fruit production; medical plant